2023
DOI: 10.1002/ps.7607
|View full text |Cite
|
Sign up to set email alerts
|

First report of target‐site resistance to ACCase‐inhibiting herbicides in Bromus tectorum L.

Abstract: BackgroundThe prevalent and repeated use of acetyl‐coenzyme A carboxylase (ACCase)‐inhibiting herbicides for Bromus tectorum L. control in fine fescue (Festuca L. spp) grown for seed has selected ACCase‐resistant B. tectorum populations. The objectives of this study were to (1) evaluate the response of nine B. tectorum populations to the ACCase inhibitors clethodim, sethoxydim, fluazifop‐P‐butyl, and quizalofop‐P‐ethyl and the acetolactate synthase (ALS) inhibitor sulfosulfuron and (2) characterize the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Research into the molecular resistance mechanisms to ACCase‐inhibiting herbicides in downy brome ( Bromus tectorum L.), has shown the presence of two different mutations, and authors have suggested a multiple evolutionary origin of ACCase resistance. Mutations described correspond to Ile2041Thr and Gly2096Ala which rendered a different pattern of ACCase‐resistance (Ribeiro et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research into the molecular resistance mechanisms to ACCase‐inhibiting herbicides in downy brome ( Bromus tectorum L.), has shown the presence of two different mutations, and authors have suggested a multiple evolutionary origin of ACCase resistance. Mutations described correspond to Ile2041Thr and Gly2096Ala which rendered a different pattern of ACCase‐resistance (Ribeiro et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The population exhibited high levels of resistance to fluazifop-P-butyl (RF > 16) and sethoxydim (RF > 23) and low levels of resistance to clethodim (RF > 2) and quizalofop-P-ethyl (RF > 3). Fifteen years later, nine more ACCase-resistant B. tectorum populations were found in fine fescue seed production fields in the same area (Ribeiro et al 2023). The levels of resistance varied among the populations for clethodim (RF = 5.1 to 14.5), sethoxydim (RF = 18.7 to 44.7), fluazifop-P-butyl (RF = 3.1 to 40.3), and quizalofop-P-ethyl (RF = 14.5 to 36).…”
Section: Resistance In Bromus Tectorummentioning
confidence: 97%
“…spp.) fields in Oregon (Ball et al 2007;Ribeiro et al 2023). In 2005, Ball et al (2007 identified an ACCaseresistant B. tectorum population in a creeping red fescue (Festuca rubra L. ssp.…”
Section: Resistance In Bromus Tectorummentioning
confidence: 99%
See 1 more Smart Citation